2019
DOI: 10.1088/1748-9326/ab4b41
|View full text |Cite
|
Sign up to set email alerts
|

Projected increase in the spatial extent of contiguous US summer heat waves and associated attributes

Abstract: The frequency, intensity and duration of heat waves are all expected to increase as the climate warms in response to increasing greenhouse gas concentrations. The focus of this study is on another dimension of heat waves, their spatial extent, something that has not been studied systematically by researchers but has important implications for associated impacts. Of particular interest are spatially contiguous heat wave regions, examined here over the conterminous US for the May-September season in both the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 49 publications
0
59
0
1
Order By: Relevance
“…Extreme temperature fluctuations in terrestrial and marine systems have occurred with increasing frequency and duration over the past century, and will increase further with continued anthropogenic climate change Lyon et al, 2019;Oliver et al, 2019;Rohini et al, 2019). Marine heatwaves (MHWs) are one such example of temperature fluctuations, and are defined as "discrete prolonged anomalous warm water events" (Hobday et al, 2016) that can result in rapid population declines and reduced ecosystem functioning (Frölicher and Laufkötter, 2018;Oliver et al, 2019;Smale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Extreme temperature fluctuations in terrestrial and marine systems have occurred with increasing frequency and duration over the past century, and will increase further with continued anthropogenic climate change Lyon et al, 2019;Oliver et al, 2019;Rohini et al, 2019). Marine heatwaves (MHWs) are one such example of temperature fluctuations, and are defined as "discrete prolonged anomalous warm water events" (Hobday et al, 2016) that can result in rapid population declines and reduced ecosystem functioning (Frölicher and Laufkötter, 2018;Oliver et al, 2019;Smale et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In future work, it would be interesting to examine the predictability of the weather regimes, particularly C1, in a warming climate. On one hand, under climate change, heat waves are expected to become stronger, longer, and larger, making the more skillful forecasts of the associated circulation patterns such as C1 even more important (Lau and Nath 2014;Rasmijn et al 2018;Lyon et al 2019;Nabizadeh et al 2019;Perkins-Kirkpatrick and Lewis 2020;Kornhuber and Tamarin-Brodsky 2021). On the other hand, recent studies using the same dynamical systems-based analysis have shown that climate change can impact d and θ, thus changing the intrinsic predictability of weather regimes (Faranda et al 2019a;Scher and Messori 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating the combined spatial and temporal evolution of heat events seem to be limited to the effects of different future climates on heatwave size and duration for differing heatwave definitions (Lyon et al ., 2019; Vogel et al ., 2020). This contrasts with other aspects of atmospheric research, where schemes tracking the spatial and temporal development of weather phenomena are widely utilized—for example, storm tracking for convective storms (Dixon and Wiener, 1993; Johnson et al ., 1998; Lakshmanan and Smith, 2010).…”
Section: Introductionmentioning
confidence: 99%